2023
DOI: 10.1111/brv.12976
|View full text |Cite
|
Sign up to set email alerts
|

On the paradox of thriving cold‐water coral reefs in the food‐limited deep sea

Abstract: The deep sea is amongst the most food‐limited habitats on Earth, as only a small fraction (<4%) of the surface primary production is exported below 200 m water depth. Here, cold‐water coral (CWC) reefs form oases of life: their biodiversity compares with tropical coral reefs, their biomass and metabolic activity exceed other deep‐sea ecosystems by far. We critically assess the paradox of thriving CWC reefs in the food‐limited deep sea, by reviewing the literature and open‐access data on CWC habitats. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 286 publications
0
3
0
Order By: Relevance
“…variabilis (Maier et al, 2023). The corals in this study are also genetically different between the two regions (Zeng et al, 2017), which could explain some of the observed differences in live:reef ratios.…”
Section: Live:reef Ratios Between South Pacific Ocean Sitesmentioning
confidence: 63%
See 1 more Smart Citation
“…variabilis (Maier et al, 2023). The corals in this study are also genetically different between the two regions (Zeng et al, 2017), which could explain some of the observed differences in live:reef ratios.…”
Section: Live:reef Ratios Between South Pacific Ocean Sitesmentioning
confidence: 63%
“…Additionally, subtropical surface waters and subantarctic waters from the Southern Ocean meet near the Graveyard Seamount Complex, causing higher primary productivity than is found at the Louisville Seamount Chain (Tracey et al, 2023). Higher than average surface productivity provides greater levels of food to CWC, driving reef distribution for several species, including S. variabilis (Maier et al, 2023). The corals in this study are also genetically different between the two regions (Zeng et al, 2017), which could explain some of the observed differences in live:reef ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations already exist for the conundrum of highly productive reefs under seemingly food-limited conditions (Cathalot et al, 2015;van Oevelen et al, 2009). For example, cold-water corals typically occur at locations of increased export production (da Costa Portilho-Ramos et al, 2022;Maier et al, 2023;. Self-organization in cold-water coral reefs can be an additional explanation for how cold-water coral reefs can maintain a high productivity with many associated fauna in the deep sea, or simply an emergent characteristic of cold-water coral ecosystems.…”
Section: Mechanisms For Self-organization In Deep-sea Coralsmentioning
confidence: 99%
“…Several explanations already exist for the conundrum of highly productive reefs under seemingly food-limited conditions (van Oevelen et al, 2009;Cathalot et al, 2015). For example, cold-water corals typically occur at locations of increased export production (Wienberg and Titschack, 2017;da Costa Portilho-Ramos et al, 2022;Maier et al, 2023). Selforganization in cold-water coral reefs can be an additional explanation for how coldwater coral reefs can maintain a high productivity with many associated fauna in the deep sea, or simply an emergent characteristic of cold-water coral ecosystems.…”
Section: Mechanisms For Self-organization In Deep-sea Coralsmentioning
confidence: 99%
“…By forming regular patterns in space, an organism can extend the area from which it extracts resources, allowing it to thrive in resource limited circumstances (Rietkerk et al, 2004;Rietkerk and van de Koppel, 2008;Bastiaansen et al, 2020). Spatial self-organization should thus be added to the list of explanations for the conundrum (Maier et al 2023) of highly productive cold-water coral reefs in the resource limited deep-sea (chapter 2 and 4).…”
Section: Self-organization In the Deep-sea: A Gradual Change Or Sudde...mentioning
confidence: 99%